If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(5x+90)=2(x+72)
We move all terms to the left:
4(5x+90)-(2(x+72))=0
We multiply parentheses
20x-(2(x+72))+360=0
We calculate terms in parentheses: -(2(x+72)), so:We get rid of parentheses
2(x+72)
We multiply parentheses
2x+144
Back to the equation:
-(2x+144)
20x-2x-144+360=0
We add all the numbers together, and all the variables
18x+216=0
We move all terms containing x to the left, all other terms to the right
18x=-216
x=-216/18
x=-12
| -2/5w-5/3=7/3w-1 | | 100+100+80+d=360 | | 0=x6 | | 2(v+3)=-2(6v-1)+2v | | 1/3(x+28)=4/5x | | -x^3=343 | | 4x²+2x-12=0 | | 2(y+1)=6y-34 | | -x3=343 | | 16a=180 | | 6.x2-4x+27=0 | | 17-20z=-13-18z | | 3(2x-3)=4x-1 | | x+30=510+30=5 | | -2n-10=-5n+2+6n | | -5+10+9x+1=180 | | -5+10=9x+1 | | X^2-6x-62=-10 | | 2x+48+x-8+x=180 | | x+30=510+30=540 | | 8x+7x-66=44-7x | | -2m+7-5=20 | | 63=b-1.5 | | 32x-3=4x-1 | | 5(i-4)+6=8(i+7)-2(3i+5) | | x+2~7=4 | | -4-2(6x-2)^2=-86 | | 2i+5=2(i-7) | | 2x+43/10=0 | | 2x+328-3x)=3 | | 0=35x-4.9x^2 | | 125x=12.8 |